Гібридні моделі і методи прогнозування рекомендацій для інтернет-магазину - Шварц, Михайло Євгенійович (Національний університет "Львівська політехніка", 2019)
У дисертаційній роботі розв’язано науково-прикладне завдання розроблення гібридних моделей і методів прогнозування рекомендацій для інтернет-магазину. Удосконалено метод розрахунку коефіцієнтів подібності векторів для методу зваженої суми, який на відміну від існуючих, використовує демографічні характеристики користувачів, що дозволяє підвищити точність прогнозування рекомендацій. Вперше на основі концепції застосування в одному методі категоріальної, мішаної і числової кластеризації розроблено метод пошуку груп користувачів, який адаптується до розрідженості матриці користувач-предмет. Отримав подальший розвиток метод мішаної кластеризації, який використовується для кластеризації категоріально-числових векторів профілів користувачів і, на відміну від існуючих, дає можливість автоматично вибирати центри кластерів і дозволяє зменшити час пошуку груп користувачів при високій точності виділення груп. Отримав подальший розвиток метод збільшення різноманітності рекомендованих предметів, який дозволяє врахувати оцінки подібних предметів в околі предметів активного користувача і вирішує проблему "довгого хвоста". Удосконалено метод надання рекомендацій користувачу рекомендаційної системи, який, на відміну від існуючих, базується на концепції асоціативних правил, враховує інтереси існуючих у системі користувачів, дає можливість надавати рекомендації новому користувачу, пропонувати користувачу супутні предмети. Для пошуку асоціативних правил метод використовує адаптивну стратегію ітеративного збільшення підтримки асоціативних правил. Проведено експериментальні дослідження розроблених моделей і методів. В диссертационной работе решено научно-прикладное задание разработки гибридных моделей и методов прогнозирования рекомендаций для интернет- магазина. Усовершенствован метод расчета коэффициентов сходства векторов для метода взвешенной суммы, который в отличие от существующих, использует демографические характеристики пользователей и позволяет повысить точность прогнозирования рекомендаций. Впервые на основе концепции применения в одном методе категориальной, смешанной и числовой кластеризации разработан метод поиска групп пользователей, который адаптируется к разреженности матрицы пользователь-предмет. Получил дальнейшее развитие метод смешанной кластеризации, который позволяет использовать для кластеризации категориально-числовые векторы профилей пользователей и, в отличие от существующих, автоматически выбирать центры кластеров и позволяет уменьшить время поиска групп пользователей при высокой точности выделения групп. Получил дальнейшее развитие метод увеличения разнообразия рекомендованных предметов, который позволяет учесть оценки подобных предметов в окрестности предметов активного пользователя и решает проблему "длинного хвоста". Усовершенствован метод предоставления рекомендаций пользователю рекомендательной системы, который, в отличие от существующих, базируется на концепции ассоциативных правил, учитывает интересы существующих в системе пользователей, позволяет предоставлять рекомендации новому пользователю и предлагать пользователю сопутствующие предметы. Для поиска ассоциативных правил метод использует адаптивную стратегию итеративного увеличения поддержки ассоциативных правил. Проведены экспериментальные исследования разработанных моделей и методов. In the dissertation, the scientific and practical task of developing hybrid models and methods for predicting recommendations for users of an online store has been solved. The method for calculating vector similarity coefficients for the weighted sum method, which, unlike the existing ones, uses the demographic characteristics of users, improves the accuracy of forecasting recommendations, has been improved. For the first time, based on the concept of using categorical, mixed, and numerical clustering in a single method, a method of searching for user groups has been developed that adapts to the sparseness of the user-subject matrix. The mixed clustering method was further developed, which allows using categorical-numerical user profile vectors for clustering and, unlike existing ones, automatically select cluster centers and reduces the search time for user groups with high accuracy of group allocation. The method of increasing the variety of recommended items, which allows to take into account the estimates of such items in the vicinity of the items of the active user and solves the problem of the “long tail”, was further developed. The method of providing recommendations to the user of the recommendation system has been improved, which, unlike the existing ones, is based on the concept of association rules, takes into account the interests of the users existing in the system, allows to give recommendations to the new user, to offer the user related items. To search for association rules, the method uses an adaptive strategy of iterative increase in support for association rules. Experimental studies of the developed models and methods were carried out. A model and method for increasing the diversification of goods and services provided by an online store have been developed. With respect to online shopping, diversification means expanding the range of products and services that an online store offers to a potential buyer. The referral system offers the buyer top-N items, goods or services. However, the recommendation prediction algorithm predicts items with similar characteristics or high popularity. Diversification greatly helps to solve these problems and increase the profits of the online store.
Гибридные модели и методы прогнозирования рекомендаций для интернет-магазина
Hybrid models and methods for predicting recommendations for online store
Keywords: інтернет-магазин; прогнозування рекомендацій; кластеризація; демографічно-рейтинговий профіль користувача; рекомендаційна система; интернет-магазин; прогнозирование рекомендаций; кластеризация; демографическо-рейтинговый профиль пользователя; рекомендательная система; online store; predicting recommendations; clustering; demographic-rating profile of user; recommender system; 004.89